Implementation of European Union funds in health promotion on metropolitan city of Warsaw basing on HEPRO Project - Olejniczak, Dominik (Polish Journal of Public Health, 2011)
Introduction. Poland’s accession to the European Union has given opportunity to take advantage of EU structural funds. Effective implementation of European funds, especially in the field of public health and health promotion may have a strong impact on the improvement of the population’s health. Aim. The aim of this publication is to describe health promotion activities carried out in the city of Warsaw basing on HEPRO research. Material and methods. The analyzed data include the documentation of HEPRO research, which took place in 2006-2007. Results. Results of the research have shown that implementation of health promoting initiatives in the city of Warsaw is reasonable and desirable. These initiatives have positive influence on health of population and are a chance for improving health. Health promoting initiatives have interdisciplinary character and can be performed by various institutions whose activities should be coordinated for the best results. All the actions should be undertaken based on the approved plan of health promoting initiatives in the agglomeration. Conclusion. The conclusion is that health promoting initiatives can be one of main sources of money for health promotion. They do not have only clinical character, but also include other sectors, such as medical statistics. Health policy, as part of health promotion, can be one of main areas of implementing European Union funds.